2019
DOI: 10.3389/fphar.2019.01144
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vasodilators From Herbal Components by a Transcriptome-Based Functional Gene Module Reference Approach

Abstract: Vasodilatation is one of the key therapeutic strategies for the treatment of various cardiovascular diseases with high blood pressure. Therefore, development of drugs assisting blood vessel dilation is promising. It has been proven that many drugs display definite vasorelaxant effects. However, there are very few studies that systemically explore the effective vasodilators. In this work, we build a transcriptome-based functional gene module reference approach for systematic pursuit of agents with vasorelaxant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…3 Although useful, they fail to detect biological processes that are distributed across an entire fibrogenic network. In the present study, following our previous work, 27 a transcriptome-based approach, TFGMR, was proposed to systemically investigate the effects of natural products on CF.…”
Section: ■ Discussionmentioning
confidence: 99%
“…3 Although useful, they fail to detect biological processes that are distributed across an entire fibrogenic network. In the present study, following our previous work, 27 a transcriptome-based approach, TFGMR, was proposed to systemically investigate the effects of natural products on CF.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The ES values within [−1 1] could evaluate the overrepresentation of CFGM at the extremes (bottom or top) of each transcriptional profile. The significance of ES values was estimated by comparing these with a set of ES NULL values calculated randomly ( Li et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…TCM102 database is also widely utilized in research to discover new indications of herbal compounds based on the systems-based approach (18,19). For example, Li et al (18) have identified several vasodilators from TCM102 database.…”
Section: Transcriptome-based Identification Of Novel Indications For ...mentioning
confidence: 99%
“…TCM102 database is also widely utilized in research to discover new indications of herbal compounds based on the systems-based approach (18,19). For example, Li et al (18) have identified several vasodilators from TCM102 database. They first generated two gene signatures that involved in positive and negative regulation of blood vessel diameter by using databases GO and SEEK (search-based exploration of expression compendia) (112).…”
Section: Transcriptome-based Identification Of Novel Indications For ...mentioning
confidence: 99%
See 1 more Smart Citation